WALL-EYED MONOCULAR INTER-NUCLEAR OPHTHALMOPLEGIA (WEMINO) SYNDROME, A RARE DECISIVE MANIFESTATION OF AN ISOLATED UNILATERAL PONTINE STROKE - Ullah, Rafiq; Yasir, Muhammad; Sarafaraz, Walid; Hussain, Rafaqat; Rashid, Nasar (Journal of Ayub Medical College Abbottabad, 2021)
Isolated unilateral pontine infarction is an uncommon occurrence. It may bring a complex neuro-ophthalmic manifestation to the clinicians, making the on-spot-diagnosis a hard challenge. Wall-eyed monocular inter-nuclear ophthalmoplegia (WEMINO) syndrome is a rare variant of inter-nuclear ophthalmoplegia which also includes ipsilesional exotropia. The literature seems deficient in documenting WEMINO syndrome the primary presentation of isolated unilateral pontine stroke. The location of the causative lesion of WEMINO syndrome is a hot topic. Here, we discuss a case of WEMINO syndrome, a rare presentation of limited unilateral pontine stroke and its responsible lesion. To the best of our knowledge this is the first reported case from Pakistan. A short literature review has also been presented on the anatomy, pathophysiology and various manifestations of isolated unilateral pontine lesion in the region of medial longitudinal fascicules (MLF). Hence, this article enhances the understanding of clinicians regarding the responsible lesions limited to pons and its various manifestations, in order to enable clinicians to pick them in the early opportunity.